Teor de Potássio em mostos de uvas Vitis Vinifera na Campanha Gaúcha - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Potassium is the second most used fertilizer in fertigation, in addition to being the nutrient exported in greater quantity by the vine, having great importance in oenology for influencing the pH of wines. The presence of excess potassium in wines significantly increases the pH, bringing inconvenience, due to the microbial instability generated and greater chances of oxidation, loss of color in red wines, in addition to making it difficult to clean the wines, these compounds when united form potassium tartrate. calcium and potassium bitartrate. Wines with high pH values are mainly the result of grapes with excessive potassium levels and can compromise their conservation. Musts with high pH require, then, prior correction usually made with tartaric acid. The excess of potassium in the wine results in an increase in the pH and a reduction in the total acidity, this influence on these physical-chemical parameters of importance for the quality and microbiological stability of the wines, since they are directly related to the stability of the color of red wines, in that the stability of anthocyanins is dependent on a pH below 4.0. Thus, in this study, samples were taken from a UNIPAMPA database. They were selected years ago from commercial vineyards in the cities of Dom Pedrito, Bagé, Maçambará, Rosário do Sul, Uruguaiana and Santana do Livramento, and from the cultivars Cabernet Sauvignon, Chardonnay, Gewürztraminer, Marselan and Pinot Noir, in the 2021, 2022 and 2023. For data processing, data on reducing sugars, pH and potassium were considered. The data obtained demonstrated in the results of the analyzes carried out that the determining factor for the accumulation of potassium in the must seems to be the longer cycle. And that, with a higher concentration of potassium, this is reflected in the higher pH values. The decision to use different harvests of the same cultivars is also justified in order to understand whether the harvest factor is determinant in the accumulation of potassium in the grape must.
Keywords: Uvas; Vitis Vinifera; Campanha Gaúcha; Minerais; Grapes; Minerals; CNPQ::CIENCIAS AGRARIAS